2020
DOI: 10.1002/ijfe.1996
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability of the Turkish current account: Smooth structural break and asymmetric adjustments

Abstract: In this study, we investigate the sustainability of Turkish current account to GDP ratio in the long run by testing the null hypothesis of a unit root against the alternative of the smooth structural break with sign and/or size nonlinearity. Using nonlinear unit root tests, we find strong evidence in favour of the sustainability of Turkish current account deficit after taking into account both the smooth structural break and asymmetric speed of adjustment towards mean values. The core of our conclusion is twof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Therefore, we can conclude that increases in financial risks play a more important role than economic risks in increasing CDS premium. This result is expected since Turkish economy in the analyzed period can be characterized as a fastgrowing economy with predominantly dependent on foreign financing which leaves Turkish economy more fragile against the changing risk appetite of foreign investors (for further readings see Telli et al, 2008;Özatay, 2008;Macovei, 2009;Uygur 2010;Özatay, 2016;Ozer &Yeldan, 2016;Abioglu et al, 2020). Thus, we can say that the effects of increases in financial risks on CDS spreads are higher than the effects of increases in economic risks for Turkey that is vulnerable to sudden stops.…”
Section: Data and Empirical Resultsmentioning
confidence: 92%
“…Therefore, we can conclude that increases in financial risks play a more important role than economic risks in increasing CDS premium. This result is expected since Turkish economy in the analyzed period can be characterized as a fastgrowing economy with predominantly dependent on foreign financing which leaves Turkish economy more fragile against the changing risk appetite of foreign investors (for further readings see Telli et al, 2008;Özatay, 2008;Macovei, 2009;Uygur 2010;Özatay, 2016;Ozer &Yeldan, 2016;Abioglu et al, 2020). Thus, we can say that the effects of increases in financial risks on CDS spreads are higher than the effects of increases in economic risks for Turkey that is vulnerable to sudden stops.…”
Section: Data and Empirical Resultsmentioning
confidence: 92%
“…As a result, the author concluded that a sustainable CA is consistent with the sustainability of external debts. Other notable studies that evaluate CA sustainability, but are not limited to, include Trehan and Walsh (1991), Wu et al (1996), Wu (2000), Christopoulos and León‐Ledesma (2010), Holmes et al (2010), Chen (2011), Andre et al (2018), Hasdemir et al (2019), and Abioglu et al (2021).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…For example, studies such as Wu et al (2001), Arize (2002), Irandoust and Ericsson (2004), Baharumshah et al (2003), Baharumshah et al (2005), Fountas and Wu (1999), Shastri et al (2018b), Afonso et al (2019), and Dash (2020) employed time-series and panel cointegration tests to assess the current account sustainability of various countries and regions. On the other hand, some studies, for instance, Christopoulos and León-Ledesma (2010), Holmes et al (2010), Chen (2011a, 2011b), Andre et al (2018), Hasdemir et al (2019) and Abioglu et al (2021), used linear and non-linear unit-root tests.…”
Section: Introductionmentioning
confidence: 99%